Evaluation of the activity of crude alkaloids extracts of Zingiber officinale Roscoe, Thymus vulgaris L. and Acacia arabica L. as coagulant agent in lab mice. - Al-Naqqash, Zahraa; Jawad, Abdul-Latif; Raaof, Ayyad (Iraqi Journal of Science, 2023)
As Alkaloids known for their pharmaceutical importance; this research included the extraction of crude alkaloids of three plants (Zingiber officinale Roscoe., Thymus vulgaris L. and Acacia arabica L.) and evaluate their activity as coagulant agent by using three degraded concentrations of each plant extract and tested them on lab mice through the observation of the variations in bleeding time (BT), clotting time (CT) and platelet count. The results revealed differences in the percentage of alkaloids in the plants under the study; Z. officinale extract was the higher one followed by T. vulgaris and A. arabica respectively. Z. officinale extract was also the most effective plant as coagulant factor than other two plants as it decreased both BT and CT and increased platelets count more than what T. vulgaris and A. arabica affected on blood characters mentioned before. This makes crude alkaloids extract of Z. officinale dry rhizomes is the best plant product therapeutically and commercially.